The crossroads ; food, trends, & cultural experiences/ Hashim Fadzil Ariffin - Ariffin, Hashim Fadzil (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2023)
Greetings from Bulletin FPHP - Hot & Tour! As we present this edition of our newsletter, we embark on a journey of exploration at the intriguing junction known as "The Crossroads," This theme delves into the captivating confluence of food, trends, & cultural experiences, weaving a tapestry that reflects the diversity & dynamism of our world. Within these virtual pages, we've gathered a selection of articles that shine a light on the multifaceted nature of The Crossroads. These pieces embody the essence of our theme, offering insights into the ways culinary traditions merge, trends emerge, and cultures intermingle, shaping our experiences & perspectives. We believe that the heart of The Crossroads lies not only in the content, also present the voices that contribute to it. That's why we extend a heartfelt invitation to you, our esteemed readers, to join in this exploration. Your unique viewpoints, stories, and reflections hold immense value in unraveling the complexities of this intersection. We encourage share your thoughts on how food connects cultures, tre societies, and the beauty of diversity unites us all